2008
DOI: 10.1073/pnas.0803319105
|View full text |Cite
|
Sign up to set email alerts
|

Temperature regulates limb length in homeotherms by directly modulating cartilage growth

Abstract: Allen's Rule documents a century-old biological observation that strong positive correlations exist among latitude, ambient temperature, and limb length in mammals. Although genetic selection for thermoregulatory adaptation is frequently presumed to be the primary basis of this phenomenon, important but frequently overlooked research has shown that appendage outgrowth is also markedly influenced by environmental temperature. Alteration of limb blood flow via vasoconstriction/vasodilation is the current default… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
121
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 39 publications
(41 reference statements)
4
121
1
Order By: Relevance
“…Results confirmed that the ears, limbs, and tails of warm-reared mice were significantly longer than those of siblings raised in the cold, without a change in total body mass (Serrat et al, 2008). The data did not fully support the vascular perfusion hypothesis when total bone blood flow was measured by microsphere deposition methods.…”
supporting
confidence: 54%
See 4 more Smart Citations
“…Results confirmed that the ears, limbs, and tails of warm-reared mice were significantly longer than those of siblings raised in the cold, without a change in total body mass (Serrat et al, 2008). The data did not fully support the vascular perfusion hypothesis when total bone blood flow was measured by microsphere deposition methods.…”
supporting
confidence: 54%
“…Although traditionally viewed as naturally selected adaptations for thermoregulation, at least some of the appendage differences described by Allen can be replicated experimentally by raising young animals at warm and cold temperatures throughout ontogeny. These findings suggest that Allen's "rule" might at least partially reflect phenotypic plasticity during development (Serrat et al, 2008). Such growth plasticity (which may or may not carry a thermal advantage: see Scholander, 1955;Steegmann 2007) could thus be a physiological response to an environmental stressor rather than an explicit genotypic adaptation for temperature control.…”
mentioning
confidence: 93%
See 3 more Smart Citations